The impact of firm size and its ownership on innovation cooperation in medium-high and high technology sectors in Poland = Wpływ wielkości i własności przedsiębiorstwa na współpracę innowacyjną w sektorze średnio wysokiej i wysokiej techniki w Polsce - Dzikowski, Piotr; Tomaszewski, Marek (Zielona Góra: Faculty of Economics and Management Press)
The main goal of this study is to identify the impact of firm size and its ownership on innovation cooperation in medium-high and high technology sectors in Poland between 2008-2013. The most open for innovation cooperation are large and foreign enterprises which mainly cooperate with foreign and national R&D units and universities.
Keywords: sektor średnio wysokiej techniki; sektor wysokiej techniki; współpraca innowacyjna; wielkość przedsiębiorstwa; własność przedsiębiorstwa; medium high technology; high technology; innovative cooperation; firms size; firms ownership